Analyzing the American Gender Wage Gap: Why Do Different States Have Different Wage Gaps? - Orloff, Reba Z. (Tufts Archival Research Center, 2017)
A facet of the American gender wage gap is state level variation. Why are women paid 64 cents to the male dollar in Wyoming, but 89 cents to the male dollar in New York? Utilizing regression analysis, I explore my hypothesis that certain demographic and political variables have statistically significant relationships with state level gender wage gaps. My findings confirm my hypothesis, indicating that the Hispanic population, Black population, median age, urbanization, female share of the workforce, comparable worth legislation, and women in the state legislature are significant in their associations to state level wage gaps.